RANCANGAN TRACKING MATERIAL SYSTEM UNTUK PELACAKAN DAN PEMINDAHAN KOMPONEN ANTAR GUDANG (STUDI KASUS PT. PINDAD) - Afif, Ilham; Pratikto; Sumantri, Yeni (Jurnal Rekayasa Mesin, 2024)
This journal presents the development of the Material Tracking Application at PT. Pindad. During the assembly process, some components may be rejected due to defects or non-compliance with other components from different suppliers. It is difficult to identify the origin of rejected components due to the lack of rejection data from each supplier. This issue led to the development of applications that can trace the origin of components by attaching QR codes to packages. Scanning the QR code activates the Quality Function to identify the origin of the component. QR codes were chosen because of their cost-effectiveness, low operational costs, and ease of reading compared to other Automatic Identification Procedure (Auto-ID) technologies. Another problem is the administrative process when moving parts/components from the component warehouse to the production warehouse. The recording process still uses paper-based documentation which is time-consuming and error-prone. Therefore, QR codes are also used to simplify and speed up the recording process by the security function. From designing web-based applications which are then deployed and run on Google's cloud services. The researcher then carried out a testing process with 2 stages, namely the process of verification and validation. It was found that the Material Tracking Application went well according to the researchers' expectations. There are still many opportunities for the development of this Material Tracking Application. Mainly development using other Auto-ID and different case studies in the world of manufacturing.